An Insight into Oligopeptide Transporter 3 (OPT3) Family Proteins - Kurt, Firat (Bentham Science Publ Ltd, 2021)
Background: OPT3s are involved in the transport of Fe from xylem to phloem, in loading Fe into phloem, and in the transmission of shoot-to-root iron signaling. Yet, apart from Arabidopsis, little is known about these transporters'functions in other plant species. Objective: OPT3 proteins of several plant species were characterized using bioinformatical tools. Also, a probable Fe chelating protein, GSH, was used in docking analyses to shed light on the interactions of ligand binding sites of OPT3s. Methods: The multiple sequence alignment (MSA) analysis, protein secondary and tertiary structure analyses. molecular phylogeny analysis, transcription factor binding site analyses, co-expression and docking analyses were performed using up-to-date bioinfonnatical tools. Results: All OPT3s in this study appear to be transmembrane proteins. They appear to have broad roles and substrate specificities in different metabolic processes. OPT3 gene structures were highly conserved. Promoter analysis showed that bZIP, WRKY, Dof and AT-Hook Transcription factors (TFs) may regulate the expression of OPT3 genes. Consequently, they seemed to be taking part in both biotic and abiotic stress responses as well as growth and developmental processes. Conclusion: The results showed that OPT3 proteins are involved in ROS regulation, plant stress responses, and basal pathogen resistance. They have species-specific roles in biological processes. Lastly, the transport of iron through OPT3s may occur with GSH according to the binding affinity results of the docking analyses.
KURT, FIRAT/0000-0003-0172-1953
Keywords: Glutathionc (GSH); iron; YSL; oligopeptidc transporter 3; docking; transporters